2021
DOI: 10.1021/acs.analchem.1c02842
|View full text |Cite
|
Sign up to set email alerts
|

Axial Ligand-Engineered Single-Atom Catalysts with Boosted Enzyme-Like Activity for Sensitive Immunoassay

Abstract: Inspired by the key role of the coordination environment in the catalytic activity of enzymes, a rational design of the coordination structure of active sites at the atom scale is expected to develop high-performance enzyme-like catalysts. Here, we design a simple model system involving pentacoordinated and tetracoordinated Fe–N–C single-atom catalysts (named NG-Heme and G-Heme, respectively) to investigate structure–activity relationships. NG-Heme with axial ligand-engineered Fe sites exhibits superior enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 48 publications
(62 reference statements)
0
48
0
Order By: Relevance
“…FeN 5 SAzymes with an axial coordination ligand is prepared by assembling hemin on ultrathin nitrogen-doped graphene (Figure 19d,e). [361] The interaction between Fe-N-C sites and reaction intermediates is enhanced via the push effect, boosting the ability to activate H 2 O 2 and achieving a vivid mimic of the active sites of peroxidase. With isolated active sites anchored on graphene layers, Fe-N-C SAzymes exhibit oxidase-like properties by activating O 2 into O 2 − • radicals and can be applied in biosensors.…”
Section: Enzyme-like Catalystsmentioning
confidence: 99%
“…FeN 5 SAzymes with an axial coordination ligand is prepared by assembling hemin on ultrathin nitrogen-doped graphene (Figure 19d,e). [361] The interaction between Fe-N-C sites and reaction intermediates is enhanced via the push effect, boosting the ability to activate H 2 O 2 and achieving a vivid mimic of the active sites of peroxidase. With isolated active sites anchored on graphene layers, Fe-N-C SAzymes exhibit oxidase-like properties by activating O 2 into O 2 − • radicals and can be applied in biosensors.…”
Section: Enzyme-like Catalystsmentioning
confidence: 99%
“…As an emerging nanomaterial, the application of SAzymes for tumor cell detection is an efficient solution. Xu Weiqing et al [18] . then designed five‐ligand and four‐ligand Fe−N−C SAzymes and experimentally demonstrated that the five‐ligand Fe−N−C SAzymes can achieve higher catalytic activity due to their additional axial ligands a colorimetric sensing system of immunosorbent carcinoembryonic antigen was constructed for the sensitive detection of cancer cells.…”
Section: Biosensing Detectionmentioning
confidence: 99%
“…As an emerging nanomaterial, the application of SAzymes for tumor cell detection is an efficient solution. Xu Weiqing et al [18] then designed five-ligand and four-ligand FeÀ NÀ C SAzymes and experimentally demonstrated that the five-ligand FeÀ NÀ C SAzymes can achieve higher catalytic activity due to their additional axial ligands a colorimetric sensing system of immunosorbent carcinoembryonic antigen was constructed for the sensitive detection of cancer cells. However, there are two problems with SAzymes: first, they have low dispersion in solution [83] and tend to aggregate without achieving higher catalytic activity; second, they do not have the structure to specifically recognize biomolecules.…”
Section: Cancer Cell Detectionmentioning
confidence: 99%
See 2 more Smart Citations